Flexible Implementation of the BASIL CURE. Issue 5 (5th August 2019) - Roberts, Rebecca; Hall, Bonnie; Daubner, Colette; Goodman, Anya; Pikaart, Michael; Sikora, Arthur; Craig, Paul
Abstract: Course‐based Undergraduate Research Experiences (CUREs) can be a very effective means to introduce a large number of students to research. CUREs are often an extension of the instructor's research, which may make them difficult to replicate in other settings because of differences in expertise or facilities. The BASIL (Biochemistry Authentic Scientific Inquiry Lab) CURE has evolved over the past 4 years as faculty members with different backgrounds, facilities, and campus cultures have all contributed to a robust curriculum focusing on enzyme function prediction that is suitable for implementation in a wide variety of academic settings. © 2019 International Union of Biochemistry and Molecular Biology, 47(5):498–505, 2019.